Toward stroke‐free coronary surgery: The role of the anaortic off‐pump bypass technique. Issue 4 (27th January 2021) - Ramponi, Fabio; Seco, Michael; Brereton, Russel John Legay; Gaudino, Mario F. L.; Puskas, John D.; Calafiore, Antonio M.; Vallely, Michael P.
Abstract: Surgical coronary revascularization remains the preferred strategy in a significant portion of patients with coronary artery disease due to superior long‐term outcomes. However, there is a significant risk of perioperative neurologic injury that has influenced guideline recommendations. These complications occur in 1%–5% of patients, ranging from overt neurologic deficits with permanent disability, to subtle cerebral defects noted on neuroimaging that may result in slow cognitive and functional decline. The primary mechanism by which these events occur is thromboembolism from manipulation of the ascending aorta. This occurs during cardiopulmonary bypass, aortic cross‐clamping, and partial occlusion clamping (side clamp). Elderly patients and patients with aortic atheroma are, therefore, at significantly increased risk. Initial surgical techniques addressed this by aggressively debriding or replacing the ascending aorta during coronary artery bypass grafting (CABG). Strategies then moved toward minimizing aortic manipulation through pump‐assisted beating heart surgery and off‐pump surgery with partial occlusion clamping or proximal anastomosis devices. Finally, anaortic off‐pump CABG aims to avoid all manipulation of the ascending aorta through advanced off‐pump grafting techniques combined with in situ and composite grafts. This has been demonstrated to result in the greatest reduction in risk. Establishing successful anaortic off‐pump CABG programs requires subspecialization and focused interest groups dedicated to advancing CABG outcomes.